Rebuilding the donbass: the Impact of Nazi-Occupation on workers, engineers and the economic development of the Post-War Soviet Union in late Stalinism - Penter, Tanja (Social Movements and the Change of Economic Elites in Europe after 1945, 2018)
The case of the Soviet Union looks at first sight to be a kind of dual ‘deficit story’ in terms of the role social movements played in the post-war cleansings of economic elites who collaborated with the Nazis during the period of German occupation in World War II. Firstly, due to the specific structure of the Soviet command economy and the lack of private enterprises, it seems rather difficult to identify the ‘economic elites’ who personally profited from the German occupying regime in local societies. Secondly, the late Stalinist post-war order allowed neither the formation of independent social movements nor the participation of social movements in cleansing policies. The role of trade unions under late Stalinist rule continued to be rather marginal.